FINANCING OF VOCATIONAL EDUCATION IN UZBEKISTAN DUE TO EXTRABUDGETARY FUNDS: PROBLEMS AND PROSPECTS (World Economics and Finance Bulletin, 2023)
This article is devoted to the analysis of the sources of financing of vocational education. Moreover, it studies the opinions of foreign scholarseconomists on the education financing. In addition, the article contains considerations regarding the relevance of financing vocational education due to extrabudgetary funds and its impact on the national economy
Keywords: Education; vocational education; financing